2002
DOI: 10.1023/a:1024829328204
|View full text |Cite
|
Sign up to set email alerts
|

Sociomedical indicators in the cholera epidemic in Ferrara of 1855

Abstract: The historical report on the cholera epidemic of 1855, conserved in Ferrara City's archives allowed us to verify the probable relation between the environment and epidemic in a broad sense, using log-linear analysis and multiple logistic regression. Two thousand and thirty-three cases were analyzed and the quantitative/qualitative variables available from the report were analyzed in relationship with mortality and morbidity rates, considered as response variables. From the analysis of the quantitative variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Interestingly, a group of modern researchers recovered historical archives in Ferrara, Italy, which also suffered from another cholera epidemic in 1855 (Scapoli et al, 2002). They analysed the data in these archives using modern statistical methods and found that ‘the better kept houses in the better parts of the town had less cholera morbidity and especially mortality’, supporting a miasma theory.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
“…Interestingly, a group of modern researchers recovered historical archives in Ferrara, Italy, which also suffered from another cholera epidemic in 1855 (Scapoli et al, 2002). They analysed the data in these archives using modern statistical methods and found that ‘the better kept houses in the better parts of the town had less cholera morbidity and especially mortality’, supporting a miasma theory.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
“…Interestingly, a group of modern researchers recovered historical archives in Ferrara, Italy, which also suffered from another cholera epidemic in 1855 (Scapoli et al, 2002). They analysed the data in these archives using modern statistical methods and found that 'the better kept houses in the better parts of the town had less cholera morbidity and especially mortality', supporting a miasma theory.…”
Section: Lesson 3: Better Research Appraisal Is In Urgent Needmentioning
confidence: 99%
“…In Italy, before the unification in 1861, epidemiology developed within the context of public health [ 66 ]. In particular, based on either the miasmatic or the epidemiological-materialistic paradigm of epidemics, scientists developed theories to interpret the cholera outbreaks periodically striking the Italian peninsula [ 67 - 69 ]. These efforts contributed to the identification of the Vibrio cholerae bacillus in Florence by Filippo Pacini in 1854 [ 70 ].…”
Section: Scenario 3: Italianmentioning
confidence: 99%